Validation of a low-cost portable 3-dimensional face scanner - Liu, Catherine (Imaging Sci Dent, 2019)
PURPOSE: The goal of this study was to assess the accuracy and reliability of a low-cost portable scanner (Scanify) for imaging facial casts compared to a previously validated portable digital stereophotogrammetry device (Vectra H1). This in vitro study was performed using 2 facial casts obtained by recording impressions of the authors, at King's College London Academic Centre of Reconstructive Science. MATERIALS AND METHODS: The casts were marked with anthropometric landmarks, then digitised using Scanify and Vectra H1. Computed tomography (CT) scans of the same casts were performed to verify the validation of Vectra H1. The 3-dimensional (3D) images acquired with each device were compared using linear measurements and 3D surface analysis software. RESULTS: Overall, 91% of the linear Scanify measurements were within 1 mm of the corresponding reference values. The mean overall surface difference between the Scanify and Vectra images was <0.3 mm. Significant differences were detected in depth measurements. Merging multiple Scanify images produced significantly greater registration error. CONCLUSION: Scanify is a very low-cost device that could have clinical applications for facial imaging if imaging errors could be corrected by a future software update or hardware revision.